Pengaruh Nikotin Selama 1-2 Minggu Terhadap Jumlah Sel-Sel Spermatosit Primer, Spermatid Pada Mencit (Mus musculus) - Rahmawati, Iis (Jurusan Keperawatan FIKES UNSOED, 2013)
The effect of cigarette smoke can spoil sperm viability and spermatogenesis. It can causehormonal condition and trigger the emergence of toxic substance on sperm that it can harm male fertility. The research design employed in this study was Post Test Only Control Group Design. The samples were adult male mus musculus. There were four groups of research subject chosen randomly after homogenization. Two groups were the control group and the other two were the experimental group. The subjects in the experimental group were injected with nicotine subcutaneously for one week and two weeks with the same dosage namely 5 mg/kg bodyweight/day. The final observation was aimed at calculating the number of primary sprematocyte, spermatid. The result of the one way Anova showed that the primary spermatocyte, spermatid had a statistically significant difference on some experimental groups (p less than 0.05). LSD test showed that there was significant difference between spermatocyt primary cells of P2 and K2; there was significant difference between spermatid cells of P1 and K2. The conclusion of this research was that nicotine caused a decrease in the number of primary spermatocyte, spermatid.